2016
DOI: 10.1177/000313481608200519
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Predict Hospital Readmission after Colorectal Surgery?

Abstract: Readmissions pose a significant hardship for patients and constitute a major quality and financial concern for hospitals. We sought to define risk factors associated with hospital readmission after colorectal surgery at a tertiary care hospital. We evaluated readmission among all patients who underwent a colorectal surgical procedure between July 16, 2007 and June 30, 2011. In a cohort of 4879 operative encounters, 492 (10%) were readmitted to the hospital within 30 days of discharge. Procedures with highest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Our findings agree with an validate those of previous studies, as preoperative steroid use, history of diabetes or depression, and complications after the index procedure have been individually identified as risk factors for readmission after general surgery procedures. 9 11 A new ileostomy and steroid use were identified as a risk factor for readmission in other patients such as those with IBD, 14 as was the case in our study. A recent systematic review identified older age, presence of comorbidities, preoperative immunosuppression, and postoperative complications as risk factors for readmission within 30 days of discharge.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our findings agree with an validate those of previous studies, as preoperative steroid use, history of diabetes or depression, and complications after the index procedure have been individually identified as risk factors for readmission after general surgery procedures. 9 11 A new ileostomy and steroid use were identified as a risk factor for readmission in other patients such as those with IBD, 14 as was the case in our study. A recent systematic review identified older age, presence of comorbidities, preoperative immunosuppression, and postoperative complications as risk factors for readmission within 30 days of discharge.…”
Section: Discussionsupporting
confidence: 68%
“…Our study builds upon previously published work 9 11 by focusing on colorectal surgery with elective ileostomy creation, with broader applicability to our specialized practice. We also provide an ileostomy-specific risk calculator (prediction model) for readmission within 30 days of discharge to help identify high-risk patients before surgery, improve physician counseling, and help address risk factors before surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-operative morbidity and the need for reinterventions, in fact, affected the risk of readmission after colorectal surgery in several studies [11, 22, 23]. Similarly, amongst our patients a strong association was found between the risk of 30-day readmission and the presence of any morbidity during the first recovery as well as the need for re-interventions.…”
Section: Discussionsupporting
confidence: 77%
“…[1][2][3][4] In addition, quality measures, such as prolonged hospital length of stay and unplanned readmissions, are more prevalent among patients with multiple comorbidities and those individuals who experience a postoperative complication. [5][6][7] Equally as important, the incidence of perioperative complications may cause a reduction in both quality of life and overall survival. [8][9][10][11] The wideranging impact of postoperative complications underscores the need for appropriate preoperative risk stratification to improve patient selection, and to educate and allow for informed patient consent.…”
mentioning
confidence: 99%